Work-Family Conflict and Burnout in Police Work: The Moderating Effect of Psychological Capital - Fathoni Cahyono, Aryo Bima; Kadiyono, Anissa Lestari; Supriyatin, Tintin; Anisah, Elis (Universitas Brawijaya, Indonesia, 2025)
Police work is considered one of the professions most susceptible to stress. Sustained stress will cause burnout and negatively affect work and other aspects of an individual's life. Several problems, such as work-family conflicts, can also exacerbate this condition. This study aims to determine the role of psychological capital as a moderator of the effect of work-family conflict on burnout in Mobile Brigade Corps/Brimob members. The study used a quantitative design, with the research subjects being 117 Mobile Brigade Command members who are married and have children. The sampling method employed was random probability sampling, ensuring that each member of the target population had an equal chance of being selected. Data were collected by distributing questionnaires containing the Maslach Burnout Inventory-Human Services Survey, Work-Family Conflict Scale, and Psychological Capital Questionnaire. The analysis technique employed descriptive analysis and inferential analysis in the form of simple linear regression and interaction tests using the JASP application. This study hypothesizes that work-family conflict may significantly affect burnout, with psychological capital potentially serving as a moderating factor in the model. The findings of this study have important theoretical and practical implications. Theoretically, the study contributes to understanding burnout mechanisms within high-stress professions, particularly law enforcement. Practically, the results can inform policy and intervention strategies aimed at reducing burnout by strengthening psychological capital among Mobile Brigade Corps personnel.